Melampsora salicis-michelsonii sp. nov. on Salix michelsonii and Melampsora salicis-cavaleriei on Salix serrulatifolia from China - Wang, Li-Li; Li, Ke-Mei; Liu, Yun; Tian, Cheng-Ming (Phytotaxa, 2020)
Based on morphological and phylogenetic analyses, two Melampsora species on willows collected in China were identified and described. One species, Melampsora salicis-michelsonii sp. nov. on Salix michelsonii, is characterized by uredinia amphigenous to mainly hypophyllous; urediniospores globoid to ellipsoid, echinulate; paraphyses capitate, clavate, intermixed, sometimes thickened at apex; telia amphigenous to mainly epiphyllous, and teliospores subepidermal with evenly thickened wall. Phylogenetically, the new species forms a new monophyletic clade with high support values 93/0.99 (ML/BI). Another species on Salix serrulatifolia is mainly characterized by epiphyllous uredinia and identified as Melampsora salicis-cavaleriei, of which phylogenetic analysis was performed and reported for the first time herein.